The PsychSimCentre: teaching out‐of‐hours psychiatry to non‐psychiatrists. (28th May 2015) - Ajaz, Ali; David, Rhodri; Bhat, Mohan
Summary: Background: Junior doctors have limited experience in psychiatry before starting their training placements. The out‐of‐hours setting offers specific challenges, and trainees are expected to cope despite being underprepared. We hyphothesised that simulation‐based training would increase trainees' competence and confidence in approaching high‐risk out‐of‐hours scenarios. Methods: A pilot study focused upon the first cohort of psychiatry trainees joining the North East London NHS Foundation Trust in 2012. During their induction (and prior to any clinical duties) each trainee took part in five high‐risk clinical scenarios, assessed by a senior psychiatrist and service‐user representative. The trainees were required to complete a survey exploring their confidence across nine core psychiatric clinical domains, both before and after the simulation training. Results: The simulation training increased trainee confidence in all nine clinical domains. Before the simulation training, over half of the nine trainees self‐rated themselves as having 'no confidence' in six of the nine clinical competencies. After the training, confidence levels had significantly increased, with only two of the competencies scoring any 'no confidence' ratings. There were mixed feelings by trainees on the use of service‐user representatives in the training of doctors. Junior doctors have limited experience in psychiatry before starting their training placements Discussion: We found that high‐fidelity simulation training is a useful tool to prepare junior trainees in psychiatry to familiarise themselves with some of the high‐risk scenarios that they are likely to encounter during out‐of‐hour on‐call duties. We showed that this intervention increased trainees' confidence across a range of core psychiatric skills. This has significant implications in the provision of safe and effective patient care.